Arshile Gorky’s life in USA. The hard way of search of identity - Harutyunyan, Lyudmila; Dayan, Hripsime (Journal of Sociology: Bulletin of Yerevan University, 2022)
The life and formation of the great Armenian artist Arshile Gorky in the USA and the search for his own identity is examined in the traditions of the sociological theory of symbolic interactionism, based on the analysis of the rich documentary material left by the artist himself and his contemporaries. The key to understanding the essence of the artist’s identity is his statements about himself as a "child of Ararat", an artist who carries in himself the values of the images and colors of the lost homeland (Van, Khorgom). An analysis of the history of the search for identity shows that despite the socio-cultural problems caused by racist policies and the reality of early 20th century American society, Arshile Gorky remained faithful to his purpose and mission: in his paintings he was able to preserve the image of the lost homeland. He used his brush to recreate the image of Western Armenia. He did not change his national identity, and remaining faithful to the inherited principles nurtured himself "mighty as a giant, but tender at heart, like a child". With his art, Arshile Gorky was able to achieve the freedom he strived for.